Intermittent Epidural Bolus Compared with Continuous Epidural Infusions for Labor Analgesia: A Systematic Review and Meta-Analysis - George, Ronald B.; Allen, Terrence K.; Habib, Ashraf S. (Anesthesia and analgesia, 2013)
The current standard labor epidural analgesic regimens consist of a local anesthetic in combination with an opioid delivered via continuous epidural infusion (CEI). With CEI local anesthetic, doses may be large with resulting profound motor blockade potentially affecting the incidence of instrumental deliveries. In this systematic review of randomized controlled trials (RCTs), we compared the effect of intermittent epidural bolus (IEB) to standard CEI dosing with or without patient-controlled epidural analgesia on patient satisfaction, the need for manual anesthesia interventions, labor progression, and mode of delivery in healthy women receiving labor epidural analgesia. A systematic review of RCTs that compared CEI with IEB for labor analgesia was performed. The articles were evaluated for validity, and data were extracted by the authors and summarized using odds ratios (ORs), mean differences (MDs), and 95% confidence intervals (CIs). Nine RCTs were included in this systematic review. Three hundred forty-four subjects received CEI, whereas 350 subjects received IEB labor analgesia. All 9 studies were deemed to be low risk of bias. There was no statistical difference detected between IEB and CEI in the rate of cesarean delivery (OR, 0.87; 95% CI, 0.56-1.35), duration of labor (MD, -17 minutes; 95% CI, -42 to 7), or the need for anesthetic intervention (OR, 0.56; 95% CI, 0.29-1.06). IEB did result in a small but statistically significant reduction in local anesthetic usage (MD, -1.2 mg bupivacaine equivalent per hour; 95% CI, -2.2 to -0.3). Maternal satisfaction score (100-mm visual analog scale) was higher with IEB (MD, 7.0 mm; 95% CI, 6.2-7.8). IEB is an appealing concept; current evidence suggests IEB slightly reduces local anesthetic usage and improves maternal satisfaction. Given the wide CIs of the pooled results for many outcomes, definite conclusions cannot be drawn for those outcomes, but there is also a potential that IEB improves instrumental delivery rate and need of anesthesia interventions. More study is required to conceptualize the ideal IEB regimen and investigate its effect on labor analgesia and obstetric outcomes.